Complete 1H and 13C NMR assignment and 31P NMR determination of pentacyclic triterpenic acids. Issue 6 (26th January 2017) - Dais, Photis; Plessel, Rebecca; Williamson, Kathryn; Hatzakis, Emmanuel
Abstract : In this study we report the complete and unambiguous 1 H and 13 C NMR assignment of betulinic, maslinic, oleanolic and ursolic acids by utilizing high-resolution multidimensional NMR spectroscopy. Abstract : In this study we report the complete and unambiguous 1 H and 13 C NMR assignment of betulinic, maslinic, oleanolic and ursolic acids by utilizing high-resolution multidimensional NMR spectroscopy. In addition, we developed a 31 P NMR methodology for the qualitative and quantitative analysis of these triterpenic acids. The 31 P NMR methodology was validated using standard solutions of model compounds and has excellent accuracy and repeatability. NMR spectroscopy was proved to be a powerful tool for the determination of these bioactive molecules and will be an important aid for scientists who will perform interaction studies with these compounds, as well as researchers who need to determine and quantify them at their native sources.